Regional Impacts of Russia's Accession To The World Trade Organization - Rutherford, Thomas F., 1954- 1954- (The World Bank, 2006)
In this paper we develop a computable general equilibrium model of the regions of Russia to assess the impact of accession to the World Trade Organization (WTO) on the regions of Russia. We estimate that the average gain in welfare as a percentage of consumption for the whole country is 7.8 percent (or 4.3 percent of consumption); we estimate that three regions will gain considerably more: Northwest (11.2 percent), St. Petersburg (10.6 percent) and Far East (9.7 percent). We estimate that the Urals will gain only 6.2 percent of consumption, considerably less than the national average. The principal explanation in our central analysis for the differences across regions is the ability of the different regions to benefit from a reduction in barriers against foreign direct investment. The three regions with the largest welfare gains are clearly the regions with the estimated largest shares of multinational investment. But the Urals has attracted relatively little FDI in the service sectors. An additional reason for differences across regions is quantified in our sensitivity analysis: regions may gain more from WTO accession if they can succeed in creating a good investment climate